2019
DOI: 10.32598/ajnpp.4.3.405
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Model of Elderly Psychological Well-being Based on Personality With the Mediation of Self-care, Spiritual Experiences, and Death Anxiety

Abstract: Background: The aging population is undoubtedly an optimum success created by changes in mortality decline, as well as social and economic processes. Objectives: The aim of this paper is to investigate the relationship between personality-based psychological well-being variables and the mediation of self-care, spiritual experiences, and death anxiety. Materials and Methods: The statistical population of the present correlational study included all elderly individuals, who were being taken care of in private an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…These participants showed little evidence of “death anxiety,” which has been defined as the unusual and severe anxiety concerning the process of death and events following death (Zahedi Bidgoli, Tagharrobi, Sooki, & Sharifi, 2020). Participants also discussed the positive impact of their own personality and their religious beliefs on reducing their anxieties regarding death, which supports current literature (Heidari, Arefi, & Amiri, 2019). Low levels of death anxiety in the current study may also be due to participants’ high levels of social support and perceived life satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…These participants showed little evidence of “death anxiety,” which has been defined as the unusual and severe anxiety concerning the process of death and events following death (Zahedi Bidgoli, Tagharrobi, Sooki, & Sharifi, 2020). Participants also discussed the positive impact of their own personality and their religious beliefs on reducing their anxieties regarding death, which supports current literature (Heidari, Arefi, & Amiri, 2019). Low levels of death anxiety in the current study may also be due to participants’ high levels of social support and perceived life satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…In particular, an significant , positive association between self-care and wellbeing suggests that greater self-care activity is correlated with an improvement in general well-being. This result supported by a study (14) indicates that There is a positive and significant relationship between self-care and the psychological well-being of the elderly and direct effect of self-care on the psychological wellbeing of the elderly people (standard coefficient= 0.14). Also,…”
Section: Discussionsupporting
confidence: 71%
“…The study results indicates that the highest percentage of the elderly people with ages between (65-75) years old (66.7%), while the lowest percentage of their ages is more than 85 years old (3.3%).The high percentage of participants is males (61.7%). This result is reinforced by a study done by Heidari A, et al (2019) (8) who indicated in their results that the majority of elderly 224 (74.6% ) were males from the total number (300) of elderly people, who were being taken care of in public and private centers in Tahran, Iran. These findings may be related to the fact that the social culture of the Iraqi citizens does not allow women's status in such a place and may be indicator for a long life of males than females ,therefore; male were more than female and they were more among age group (65-75) years who live in the nursing home.…”
Section: Discussionmentioning
confidence: 84%